J Proteomics Bioinform 2019
DOI: 10.35248/0974-276x.19.12.502
|View full text |Cite
|
Sign up to set email alerts
|

The Quiescent Metabolic Phenotype of Glioma Stem Cells

Abstract: Introduction: Glioblastoma (GBM) is the most common primary malignant brain tumor in humans and, even with aggressive treatment that includes surgical resection, radiation (IR), and chemotherapy administration, prognosis is poor due to tumor recurrence. There is evidence that within GBMs a small number of glioma stem-like cells (GSLCs) exist, which are thought to be therapy resistant and are thus capable of repopulating a tumor after treatment. Like most cancers, GBMs largely employ aerobic glycolysis to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Consistent with our results, GSCs have been characterized by ample metabolic heterogeneity, exhibiting both glycolytic/oxidative characteristics [ 29 , 65 , 66 ]. Surprisingly, GBM27 exhibited a highly oxidative phenotype, at odds with Warburg’s central hypothesis of dysfunctional mitochondria; the presence of such metabolic subpopulations will need to be addressed to prevent tumor recurrence after antiglycolytic therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, GSCs have been characterized by ample metabolic heterogeneity, exhibiting both glycolytic/oxidative characteristics [ 29 , 65 , 66 ]. Surprisingly, GBM27 exhibited a highly oxidative phenotype, at odds with Warburg’s central hypothesis of dysfunctional mitochondria; the presence of such metabolic subpopulations will need to be addressed to prevent tumor recurrence after antiglycolytic therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Tumor cells metabolic reprogramming, also known as the Warburg effect, refers to tumor cells preferring glycolysis rather than the tricarboxylic acid cycle even with adequate oxygen. 86 In contrast to GBM cells, the metabolic profile of GSCs, including lower glycolytic, lower extracellular acidification rate, less oxygen consumption and maximal respiratory capacities, 87 is more quiescent. It should be noted that recent studies reported different metabolic phenotypes of GSCs.…”
Section: Metabolic Phenotype Of Gscsmentioning
confidence: 99%
“…Moreover, GSCs present globally lower levels of metabolites (such as GTP and ATP), nonessential amino acids, fructose 6-phosphate, and fructose 1,6-bisphosphate. However, metabolites belonging to the pentose phosphate and galactose metabolism, glutaminolysis, and the citric acid cycle are present at high levels in GSCs [ 114 ]. Notably, the metabolic profile reflects GSC subtype identity.…”
Section: Glioblastoma Multiformementioning
confidence: 99%